STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM IMPLEMENTASI DISIPLIN POSITIF: STUDI KUALITATIF DI SDN 02 CIKAWUNG KABUPATEN BANYUMAS - Isna Nur Istiqomah; Siswadi Siswadi (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
The shift in educational paradigms from punitive to positive discipline requires a strategic role for principals in managing changes in school culture toward a more humanistic and educative one. This study aims to analyze the principal's leadership strategies in implementing positive discipline for teachers and students at SDN 02 Cikawung, Banyumas Regency, which integrates local wisdom values. Using qualitative descriptive methods, data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed using the interactive model of Miles, Huberman, and Saldana. The results revealed that the principal fulfills his role as educator, manager, and supervisor through three key strategies: internalizing values ​​through role models, strengthening teacher capacity through reflective coaching, and creating a child-friendly school ecosystem. A unique finding of this study is the application of the "School Community Consultation" approach as an effective conflict resolution mechanism in building mutual understanding. The study's conclusions confirm that the successful implementation of positive discipline is highly dependent on the consistent leadership of the principal in facilitating the transformation of the school community's mindset from external control to intrinsic awareness and motivation. ABSTRAK Pergeseran paradigma pendidikan dari pendekatan disiplin punitif menuju disiplin positif menuntut peran strategis kepala sekolah dalam mengelola perubahan budaya sekolah yang lebih humanis dan edukatif. Penelitian ini bertujuan untuk menganalisis strategi kepemimpinan kepala sekolah dalam mengimplementasikan disiplin positif pada guru dan siswa di SDN 02 Cikawung, Kabupaten Banyumas, yang mengintegrasikan nilai-nilai kearifan lokal. Menggunakan metode deskriptif kualitatif, data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan studi dokumentasi, kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldana. Hasil penelitian mengungkapkan bahwa kepala sekolah menjalankan peran sebagai edukator, manajer, dan supervisor melalui tiga strategi kunci: internalisasi nilai melalui keteladanan, penguatan kapasitas guru berbasis coaching reflektif, dan penciptaan ekosistem sekolah yang ramah anak. Temuan unik dari studi ini adalah penerapan pendekatan "Rembug Warga Sekolah" sebagai mekanisme resolusi konflik yang efektif dalam membangun kesepahaman bersama. Simpulan penelitian menegaskan bahwa keberhasilan implementasi disiplin positif sangat bergantung pada konsistensi kepemimpinan kepala sekolah dalam memfasilitasi transformasi pola pikir warga sekolah dari kontrol eksternal menuju kesadaran dan motivasi intrinsik.